2021
DOI: 10.3390/insects12080684
|View full text |Cite
|
Sign up to set email alerts
|

Beekeeping Genetic Resources and Retrieval of Honey Bee Apis mellifera L. Stock in the Russian Federation: A Review

Abstract: The loss of honey bees has drawn a large amount of attention in various countries. Therefore, the development of efficient methods for recovering honey bee populations has been a priority for beekeepers. Here we present an extended literature review and report on personal communications relating to the characterization of the local and bred stock of honey bees in the Russian Federation. New types have been bred from local colonies (A. mellifera L., A. m. carpatica Avet., A. m. caucasia Gorb.). The main selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…There is an A. mellifera population present in the temperate zone of North-East Eurasia (Frunze et al 2021), but there is no data about the subarctic region there, although A. mellifera population inhabits the subartic region of North-Central part (Ostroverkhova et al 2020). Based on the fact that most infection cases in the temperate and subartic zone were mixed Vairimorpha species of North-Central Asia, it can be assumed that both species can also live in the North-East part of Eurasia.…”
Section: Discussionmentioning
confidence: 99%
“…There is an A. mellifera population present in the temperate zone of North-East Eurasia (Frunze et al 2021), but there is no data about the subarctic region there, although A. mellifera population inhabits the subartic region of North-Central part (Ostroverkhova et al 2020). Based on the fact that most infection cases in the temperate and subartic zone were mixed Vairimorpha species of North-Central Asia, it can be assumed that both species can also live in the North-East part of Eurasia.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, phylogenetic analysis showed that the Prioksky bees formed one cluster with a sample of A. m. caucasica from the Krasnopolyansk experimental station. The Prioksky breeding stock was bred at the Federal Beekeeping Research Centre on the basis of crossing A. m. mellifera and A. m. caucasica [41,47]. The results of a genetic analysis showed that the Prioksky sample was more consistent with the subspecies A. m. caucasica and the level of the gene pool of A. m. mellifera in it was only 1.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The cubital index for samples of A. m. mellifera was also below the standard value [39,40]. The cubital index of the Burzyan sample (AmmB), despite the fact that it was lower than standard values, corresponded to the CI for the Burzyan population of A. m. mellifera [41]. There are no standard values for other characters.…”
Section: Assessment Of Morphometric Parametersmentioning
confidence: 99%
“…The mean value of this study is smaller than the findings of Li et al (2020) where the mean Cubital Index value of Apis cerana nuluensis is 3.84 in Sulawesi, indicating that genotype and environment differences influence the size of the wing's Cubital Index. Frunze et al (2021) explained that the cubital index characteristic is used to distinguish subspecies of honey bees. Based on the Ustadi et al (2022b), research shows their findings on the differences in Cubital Index values between Apis cerana and Apis florea queen bees.…”
Section: Discussionmentioning
confidence: 99%